The Police's War Against Cyber Gamblers: A Critical Analysis of Online Gambling Handling in Parepare City - Yusril Hendra Putra; Jasmaniar Jasmaniar; Salmawati Salmawati (HORIZON PUBLIC LEGAL STUDIES, 2025)
This study aims to determine the efforts of the Parepare Police in combating online gambling crimes and the factors that hinder these efforts.The research method used by the researcher in this study is empirical legal research, in which the researcher conducted direct interviews with two members of the Makassar Police Traffic Unit. The research findings concluded that the efforts of the Parepare Police Department in combating online gambling crimes include collaborating with government authorities to conduct awareness campaigns about the dangers of online gambling through the installation of banners, posters, and video screens at specific locations in the city of Parepare, blocking websites, and restricting access to online gambling websites, as well as prohibiting internet service providers from selling internet packages for online gambling activities such as domino chips. Factors hindering efforts to combat online gambling crimes in the city of Parepare include the difficulty of tracking down bookmakers, who are generally located overseas, limitations in technology and human resources among law enforcement officials, a lack of specific and strict regulations, and economic motives and a consumerist lifestyle.